Aloe Vera–Assisted Synthesis of Dy-Doped MgNb2O6 for Sustainable Sensing and Photocatalytic Applications - N. Basavaraju; H. N. Shwetha; C. R. Ravikumar; Syed Khasim; K. B. Tan; Kiflom Gebremedhn Kelele; K. Y. Chan; H. C. Ananda Murthy (Journal of Nanotechnology)
This study introduces a novel, cost-effective, and combustion synthesis approach for synthesizing dysprosium-doped magnesium niobium oxide (Dy: MNbO) nanoparticles (NPs) via a solution combustion method utilizing aloe vera gel as a green fuel. The use of aloe vera gel not only simplifies the synthesis process but also enhances the ecocompatibility of the method, making it a significant advancement over conventional techniques. Advanced spectral techniques were employed to characterize the Dy: MNbO NPs. PXRD analysis revealed that the average crystalline size of the NPs was approximately 45 nm. The energy band gap of the synthesized Dy: MNbO NPs was determined to be in the range of 4-5 eV. SEM analysis showed the presence of distinctly agglomerated, lump-like structures. The photocatalytic performance of Dy: MNbO NPs was evaluated for the degradation of industrial dyes, specifically direct green (DG) dye, under UV light irradiation. Among different doping concentrations, the 4 mol% Dy: MNbO NPs exhibited the highest photocatalytic efficiency, achieving an 82% degradation. In comparison, the degradation rates for other doping concentrations were 58% for 2 mol%, 62% for 6 mol%, and 75% for 8 mol%. Electrochemical analyses using 4 mol% Dy: MNbO NPs as a modified electrode were performed in a 0.1 M HCl electrolyte solution. Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) confirmed the reversibility of the electrode reaction. The sample demonstrated excellent performance in electrochemical sensing applications, specifically for detecting ibuprofen and glucose molecules.